2022
DOI: 10.3389/fmolb.2022.1058602
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in ST6GAL1, one of the two α2,6-sialyltransferases, has only a minor effect on the pathogenesis of prion disease

Abstract: Prion diseases are a group of fatal neurodegenerative diseases caused by misfolding of the normal cellular form of the prion protein or PrPC, into a disease-associated self-replicating state or PrPSc. PrPC and PrPSc are posttranslationally modified with N-linked glycans, in which the terminal positions occupied by sialic acids residues are attached to galactose predominantly via α2-6 linkages. The sialylation status of PrPSc is an important determinant of prion disease pathogenesis, as it dictates the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…ST6GAL2 was the last member of the ST family to be discovered due to its low enzyme activity. It appears to exhibit narrower enzyme substrate specificity compared to ST6GAL1 (Makarava et al, 2022). Although it has been reported that ST6GAL2 can respond to a proinflammatory environment in the brain, its physiological function remains largely unknown (Lehoux et al, 2010).…”
Section: Glycoconjugates In Cnsmentioning
confidence: 99%
“…ST6GAL2 was the last member of the ST family to be discovered due to its low enzyme activity. It appears to exhibit narrower enzyme substrate specificity compared to ST6GAL1 (Makarava et al, 2022). Although it has been reported that ST6GAL2 can respond to a proinflammatory environment in the brain, its physiological function remains largely unknown (Lehoux et al, 2010).…”
Section: Glycoconjugates In Cnsmentioning
confidence: 99%
“…In addition to its involvement in prion diseases, several studies have attributed plenty of physiological roles to PrP C including anti/pro-apoptosis, metal homeostasis, anti-oxidative damage, cell adhesion and migration, signaling, immune modulation, cell differentiation, and epithelial junctions [20][21][22][23][24][25][26][27]. Yet, the PrP C physiological function is still enigmatic, since no obvious phenotype was observed in PrP C knockout mice [28,29].…”
Section: Prp C Expression and Functionsmentioning
confidence: 99%